Disentangling policy effects into causal channels - Martin Huber (IZA World of Labor, 2016)
Policy evaluation aims at assessing the causal effect of an intervention (for example job-seeker counseling) on a specific outcome (for example employment). Frequently, the causal channels through which an effect materializes can be important when forming policy advice. For instance, it is essential to know whether counseling affects employment through training programs, sanctions, job search assistance, or other dimensions, in order to design an optimal counseling process. So-called “mediation analysis” is concerned with disentangling causal effects into various causal channels to assess their respective importance.
Keywords: C21; 330; causal channels; causal mechanisms; mediation analysis; direct and indirect effects